Homelessness and social control: a typology. Issue 7 (3rd October 2018) - Johnsen, Sarah; Fitzpatrick, Suzanne; Watts, Beth
Abstract: The use of 'social control' interventions in housing and welfare policy often courts intense controversy, and never more so than when attempts are made to bring about change in the conduct of street homeless people. To date, academic scrutiny has focused on the so-called 'regulation' or 'criminalisation' of rough sleepers occupying public space, but a range of 'softer' control mechanisms are also now in evidence within homelessness support services. This paper explicates the relationship between the distinct forms of social control that have been used in this field – force, coercion, bargaining, influence and tolerance – and compares the perspectives of policy makers, frontline practitioners and homeless people regarding the appropriateness of their deployment in England. It emphasizes that the use of every one of these modes of social control, and indeed the absence of such controls, raises moral and practical dilemmas, the nuance of which is often unacknowledged in academic accounts.